PERANAN FUNGI MIKORIZA ARBUSKULA, MIKROORGANISME PELARUT FOSFAT, RHIZOBIUM SP DAN ASAM HUMIK UNTUK MENINGKATKAN PERTUMBUHAN DAN PRODUKTIVITAS LEGUM Calopogonium mucunoides PADA TANAH LATOSOL DAN TAILING TAMBANG EMAS DI PT. ANEKA TAMBANG - - Karti; - P.D.M.H.; N. R. Kumalasari; D. Setyorini (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
Latosols soil conditions are poor in nutrients and tailing of gold mine contain heavy metal causes low productivity of forage. The objective of this research to study the best combination of soil potential microorganisms and soil conditioner that can promote the growth and production of legume crops Calopogonium mucunoides Desv. Seven treatments used were A: control, B: arbuscular mycorrhizal fungi (AMF), C: AMF + Rhizobium, D: AMF + Phosphate Solubilizing Bacteria (BPF), E: AMF + Humic Acid, F: AMF + BPF + Rhizobium, G: AMF + BPF + Humic Acid + Rhizobium. Variables measured were the root dry weight, shoot dry weight, spread length, number of trifoliate leaves, the number of active root nodules, the percentage of root infection. Augmentation of soil microorganisms and soil conditioner not effective enough to improve plant growth of Calopogonium mucunoides Desv because plants can still adapt and grow well on latosols. Plants grown on tailings provide the best response is G (AMF+ Humic Acid + Rhizobium), although the rate of growth is not as good as plants grown in latosols.